Bilayered construct for simultaneous regeneration of alveolar bone and periodontal ligament. Issue 4 (7th July 2015) - Sundaram, M. Nivedhitha; Sowmya, S.; Deepthi, S.; Bumgardener, Joel D.; Jayakumar, R.
Abstract: Periodontitis is an inflammatory disease that causes destruction of tooth‐supporting tissues and if left untreated leads to tooth loss. Current treatments have shown limited potential for simultaneous regeneration of the tooth‐supporting tissues. To recreate the complex architecture of the periodontium, we developed a bilayered construct consisting of poly(caprolactone) (PCL) multiscale electrospun membrane (to mimic and regenerate periodontal ligament, PDL) and a chitosan/2wt % CaSO4 scaffold (to mimic and regenerate alveolar bone). Scanning electron microscopy results showed the porous nature of the scaffold and formation of beadless electrospun multiscale fibers. The fiber diameter of microfiber and nanofibers was in the range of 10 ± 3 µm and 377 ± 3 nm, respectively. The bilayered construct showed better protein adsorption compared to the control. Osteoblastic differentiation of human dental follicle stem cells (hDFCs) on chitosan/2wt % CaSO4 scaffold showed maximum alkaline phosphatase at seventh day followed by a decline thereafter when compared to chitosan control scaffold. Fibroblastic differentiation of hDFCs was confirmed by the expression of PLAP‐1 and COL‐1 proteins which were more prominent on PCL multiscale membrane in comparison to control membranes. Overall these results show that the developed bilayered construct might serve as a good candidate for the simultaneous regeneration of the alveolar bone and PDL. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 761–770, 2016.